Research and Development of Mathematics Teaching Material Integrated with Islamic Values: A Systematic Literature Review - Hania Rahmah; Turmudi Turmudi; Muhammad Tareq Ghifari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
Mathematics teaching material integrated with Islamic values can support the achievement of mathematics learning objectives in cognitive and affective aspects. This research aims to conduct a literature review related to the research and development of mathematics teaching material integrated with Islamic values. The method used in this research is a Systematic Literature Review (SLR) which consists of 36 studies in the period 2018 - 2022. The key question in this research is how the articles regarding research and development of mathematics teaching materials integrated with Islamic values are distributed based on year of publication, level of education, Islamic values, and mathematics topics. The results of this research show that most studies related to mathematics teaching materials integrated with Islamic values were carried out in 2020, researchers conducted a lot of research on teaching materials integrated with Islamic values at the junior high school level, teaching materials integrated with Islamic values were mostly applied to the topic of numbers, and the most widely used Islamic value is the Quran. This research is expected to be a reference to carry out further research related to mathematics teaching materials integrated with Islamic values, and using mathematics teaching material integrated with Islamic values can be the option to make the mathematics learning process more meaningful.